Infliximab treatment for Cronkhite-Canada syndrome in pregnancy: A case report - Ayano Rosemary Nakamura; Shuji Yamamoto; Yoshitsugu Chigusa; Masaki Mandai; Haruta Mogami (Case Reports in Women's Health)
Cronkhite-Canada syndrome (CCS) is a rare nonhereditary disorder characterized by gastrointestinal polyps and protein-losing enteropathy. While an increasing number of CCS cases have been reported worldwide, no documented cases involving pregnant patients could be found. Consequently, optimal management strategies for CCS during the preconception period and pregnancy remain unclear., The present report concerns the case of a 36-year-old woman with steroid-refractory CCS stabilized with gastrointestinal surgeries and infliximab, an anti-tumor necrosis factor-α (TNF-α) agent, who became pregnant. Infliximab was continued throughout pregnancy and postpartum. Despite persistent hypoalbuminemia, sh delivered a healthy infant weighing 2518 g vaginally at 38 weeks and 2 days without CCS exacerbation. Both the patient and her infant experienced an uneventful postpartum course. This case suggests that maintaining disease control with anti-TNF-α therapy in pregnant patients with CCS may contribute to optimizing maternal and neonatal outcomes.